PEMETAAN SITUASI SKALA 1:500 LOKASI DUSUN PURWOSASONO DAN DUSUN BABADAN DESA BELUK KECAMATAN BAYAT KABUPATEN KLATEN PROPINSI JAWA TENGAH - , NUR AMALINA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Situation mapping (topography) is a mapping of an area that includes horizontal and vertical dimensions to obtain the information of spatial data from the earth's surface. Field work (PKL) aims to equip students to be adept at situation mapping. Field work aims to make largescale map terrestrial situation with measurement and delineation using digital technol ogy Implementation of the situation mapping (topography) 1:500 scale mapping control framework includes maps, detailed mapping, cartography and map testing. Mapping framework in the form of map control measurements, calculations, and depictions of the control framework of horizontal and vertical control framework. Detailed mapping in the form of measurement, calculation and depiction of planimetric detail and high detail. The depiction of the map is implemented using Surpac software and ArcGIS. While map testing includes testing distance and elevation with a tolerance of 90%. . The result is a situation map (topographic) scale 1:500 location in Purwosasono and Babadan Hamlet, Beluk Village, Bayat District, Klaten Regency, Central Java Province. The map is printed on A1 size drawing paper and consists of four pieces of the map in the UTM (Universal Transverse Mercator) projection system. The distance test results are in accordance with the tolerance range, while the elevation test is not in accordance with the testing tolerance. Thus the situation maps (topographic) 1:500 scale has not passed the test.